2013
DOI: 10.1109/jphot.2013.2289988
|View full text |Cite
|
Sign up to set email alerts
|

Light Transmission Properties and Shannon Index in One-Dimensional Photonic Media With Disorder Introduced by Permuting the Refractive Index Layers

Abstract: In this paper, we have studied, with a numerical method, how introducing disorder affects the light transmission properties of 1-D photonic structures over a wide range of wavelengths. A new type of disorder is introduced by permuting the refractive index layers in the optical medium. We compared the light transmission properties of ideal photonic crystals and of disordered media with the same kind and number of scattering elements for different sample lengths. We have calculated the transmission properties, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…'We'discuss'the'optical'response,'the' fabrication'methods,'and'the'most'significant'applications'of'1D'periodic,'quasiperiodic,'and' disordered' photonic' structures.' Concerning' 1D' disordered' photonic' structures,' we' particularly' focus' on' 1D' photonic' structures' in' which' the' disorder' is' obtained' in' different' ways:' i)' with' a' random' sequence' of' high' and' low' refractive' index' layers' [45];' ii)' with' a' random'arrangement'of'a'fixed'number'of'high'refractive'layers'between'a'fixed'number'of' low'refractive'index'layers' [59,60];'iii)'with'a'random'variation'of'the'thickness'of'the'layers' in'a'periodic'structure' [61][62][63].' ' 2.…”
Section: D# 3d# 2d#mentioning
confidence: 99%
“…'We'discuss'the'optical'response,'the' fabrication'methods,'and'the'most'significant'applications'of'1D'periodic,'quasiperiodic,'and' disordered' photonic' structures.' Concerning' 1D' disordered' photonic' structures,' we' particularly' focus' on' 1D' photonic' structures' in' which' the' disorder' is' obtained' in' different' ways:' i)' with' a' random' sequence' of' high' and' low' refractive' index' layers' [45];' ii)' with' a' random'arrangement'of'a'fixed'number'of'high'refractive'layers'between'a'fixed'number'of' low'refractive'index'layers' [59,60];'iii)'with'a'random'variation'of'the'thickness'of'the'layers' in'a'periodic'structure' [61][62][63].' ' 2.…”
Section: D# 3d# 2d#mentioning
confidence: 99%
“…In 2005, Bertolotti et al experimentally observed optical necklaces [22], while in 2007 Ghulinyan observed periodic oscillations in the average transmission as a function of the sample length [23]. Recently, the Shannon index, a diversity index used in information theory and statistics [24], has been used to quantify the evenness in one dimensional photonic crystals [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the light transport depends on the dimensionality of the material structure [9]. One--dimensional systems are realized by modulating the dielectric constant in a linear arrangement, as, for example, a random multilayer [3,10,11]. For sake of clarity, a periodic alternation of the dielectric constant results in a one--dimensional photonic crystal [12--15], while a modulation of the dielectric constant that follow a deterministic generation rule gives rise to a quasicrystal [16--20].…”
mentioning
confidence: 99%